Saving a Peace : How Savings Group Build Peace. - Mcmahon, Carolyn Hall. (Tufts Archival Research Center, 2019)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy.; Framed as a development strategy based on asset accumulation and access to capital to combat liquidity constraints of the poor, savings groups may also provide important opportunities for the cultivation of peace in communities. The practices and procedures of savings groups foster highly social relationships. While some see the building of social capital as simply a positive externality of this financial intervention, this research suggests that it may be precisely these less quantifiable social outcomes that stand as the most highly valued impacts for the poor. This paper offers a point of departure for further systematic study into how the social outcomes of savings groups build peace in their surrounding communities.